Ursolic Acid Protected Lung of Rats From Damage Induced by Cigarette Smoke Extract - Lin, Li; Hou, Gang; Han, Dan; Kang, Jian; Wang, Qiuyue (Frontiers in Pharmacology, 2019)
Background: We found previously that ursolic acid (UA) administration could alleviate cigarette smoke-induced emphysema in rats partly through the unfolded protein response (UPR) PERK-CHOP and Nrf2 pathways, thus alleviating endoplasmic reticulum stress (ERS)-associated oxidative stress and cell apoptosis. We hypothesized that other UPR pathways may play similar roles in cigarette smoke extract (CSE)-induced emphysema. So, we sought to investigate the dynamic changes and effects of UPR and the downstream apoptotic pathways. Further, we investigated whether UA could alleviate CSE-induced emphysema and airway remodelling in rats, whether and when it exerts its effects through UPR pathways as well as Smads pathways. Methods: One hundred eight Sprague Dawley (SD) rats were randomly divided into three groups: Sham group, CSE group, and UA group, and each group was further divided into three subgroups, administered CSE (vehicle) for 2, 3, or 4 weeks; each subgroup had 12 rats. We examined pathological changes, analyzed the three UPR signaling pathways and subsequent ERS, intrinsic and extrinsic apoptotic pathway indicators, as well as activation of Smad2,3 molecules in rat lungs. Results: Exposure to CSE for 3 or 4 weeks could apparently induce emphysema and airway remodeling in rats, including gross and microscopic changes, alteration of mean alveolar number (MAN), mean linear intercept (MLI), and mean airway thickness in lung tissue sections. UA intervention could significantly alleviate CSE-induced emphysema and airway remodeling in rats. UA exerted its effects through ameliorating apoptosis by down regulating UPR signalling pathways and subsequent apoptosis pathways, as well as, downregulating p-Smad2 and p-Smad3 molecules. Conclusions: UA attenuated CSE-induced emphysema and airway remodeling, exerting its effects partly through regulation of three UPR pathways, amelioration downstream apoptotic pathways, and alleviating activation of Smad2 and Smad3.